2021
DOI: 10.1039/d0sc04872k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive small molecule fluorogenic probe for human heparanase

Abstract: Heparanase (HPA) is a critical enzyme involved in the remodeling of the extracellular matrix (ECM), and its elevated expression has been linked with diseases such as various types of cancer...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…The structure revealed previously unknown interactions involved in enzymatic processing and suggested using substrates with better leaving groups, e. g., halogenated coumarins. Subsequently, Cui and coworkers [73] reported that difluorocoumarins such as 36 are more efficient aglycone leaving groups for heparanase substrates, in line with our hypotheses.…”
Section: Tools For Studying Hs‐protein Interactionssupporting
confidence: 88%
“…The structure revealed previously unknown interactions involved in enzymatic processing and suggested using substrates with better leaving groups, e. g., halogenated coumarins. Subsequently, Cui and coworkers [73] reported that difluorocoumarins such as 36 are more efficient aglycone leaving groups for heparanase substrates, in line with our hypotheses.…”
Section: Tools For Studying Hs‐protein Interactionssupporting
confidence: 88%
“…Recently, we reported the first structurally defined ultrasensitive fluorogenic probe HADP (1) for detecting heparanase activity with high selectivity and sensitivity, which we used in a high-throughput screen for novel heparanase inhibitors. 15 In our initial probe design, use of the fluorogenic reporter 4-methylumbelliferone (4-MU) did not facilitate turnover of the probe by HPSE, consistent with the exclusively endo -glycosidic selectivity of HPSE enzymatic activity. However, by incorporating two electron-withdrawing fluorine atoms on the methylumbelliferone reporter, ortho to the phenolic oxygen, our HADP probe successfully elicited exo -glycosidic activity from HPSE.…”
Section: Maintextmentioning
confidence: 72%
“…However, by incorporating two electron-withdrawing fluorine atoms on the methylumbelliferone reporter, ortho to the phenolic oxygen, our HADP probe successfully elicited exo -glycosidic activity from HPSE. 15 Following this study, we developed a second fluorogenic probe for imaging heparanase activity in living cells (J.L., Z.W., and L.C., unpublished results), which also required two ortho -position fluorine atoms installed on the reporter, to elicit HPSE activity. Encouraged by these advances, we attempted to develop a near-infrared (NIR) probe for monitoring heparanase in vivo by extending the conjugation system of fluorophore, but the synthesis failed due to incompatibility of the NIR fluorophore with the chemical manipulation of the disaccharide recognition unit.…”
Section: Maintextmentioning
confidence: 99%
See 1 more Smart Citation
“…A 7-hydroxymethylcoumarin moiety was selected as the donor fluorophore, due to the possibility of functionalization onto a porphyrin scaffold and the excellent spectral overlap with the absorbance spectrum of porphyrin-based compounds (Figures S1 and S2). Additionally, 7-hydroxymethylcoumarin derivatives are also known to be fairly photostable, , including compound 1 (Figure S3), a characteristic that will importantly maximize the observed increase in fluorescence following enzymatic probe cleavage.…”
Section: Introductionmentioning
confidence: 99%